Transposon mutagenesis of atypical enteroaggregative Escherichia coli reveals a hemagglutinin-associated protein that mediates cell adhesion and contributes to the Galleria mellonella virulence - Mariane V. Monfardini; Renata T. Souza; Thais C. G. Rojas; Caroline G. Guerrieri; Cristina Orikaza; Isabel C. A. Scaletsky (Frontiers in Cellular and Infection Microbiology, 2023)
Twenty-two atypical enteroaggregative Escherichia coli isolates from a previous epidemiological study harboring EAEC virulence genes were examined for their adhesion properties. Nine strains showed a typical aggregative adherence (AA) pattern, while 13 strains showed variant AA, such as AA with lined up cells characteristic of the chain-like adhesion (CLA) and AA mainly to HeLa cells characteristic of the diffuse adherence (DA). The aggregative forming pilus (AFP) genes afpA2 and afpR were detected only in strain Q015B, which exhibited an AA/DA pattern. Using Tn5-based transposon mutagenesis on Q015B strain, we identified a 5517-bp open reading frame (ORF) encoding a predicted 1838-amino-acid polypeptide that is genetically related to a putative filamentous hemagglutinin identified in E. coli strain 7-233-03_S3_C2. Therefore, the ORF was named orfHA. The regions flanking orfHA were sequenced and two ORFs were found; upstream, an ORF that encodes a 603-amino-acid polypeptide with 99% identity to hemolysin secretion/activation proteins of the ShlB/FhaC/HecB family, and downstream, another ORF, which encodes a 632-amino-acid polypeptide with 72% identity to the glycosyltransferase EtpC. An orfHA mutant (Q015BΔorfHA) was constructed from strain Q015B. Q015BΔorfHA strain did not adhere to HeLa cells, whereas Q015BΔ orfHA transformed with a pACYC184 plasmid carrying orfHA restored the AA/DA phenotype of strain Q015B. Furthermore, the Q015ΔorfHA mutant had a marked effect on the ability of strain Q015B to kill the larvae of Galleria mellonella. Our results suggest that the AA/DA pattern of strain Q015B is mediated by a hemagglutinin-associated protein which also contributes to its virulence in the G. mellonella model.